Unlocking Soil Phosphorus: The Importance of Phosphate Solubilizers for Crop Growth - Ali, Sk Asraful; Kaur, Ramanjit; Dhyani, Vipin Chandra; Kumari, Megha; Ezing, Unti Miiri; Jha, Rashmi (Chronicle of Bioresource Management, 2024)
Phosphorus (P), the second most important macronutrient after nitrogen, plays a crucial role in plant growth and development. However, its availability in soils is often limited due to fixation in insoluble forms, resulting in low phosphorus use efficiency and negatively impacting crop yields. To enhance phosphorus availability, various agents have been identified as effective solutions, including humic substances (such as humic acid, fulvic acid, and humin), phosphate solubilizing microorganisms (PSMs), zeolite, biochar, bentonite, and polymers. These agents increase phosphorus solubility and improve soil health, thereby promoting sustainable agriculture by reducing reliance on chemical fertilizers. Their application not only boosts immediate plant growth but also contributes to long-term soil fertility and enhanced crop yields, addressing critical agricultural challenges and fostering a more resilient agricultural ecosystem. By integrating these solutions into farming practices, farmers can optimize nutrient management, improve crop productivity, and ensure environmental sustainability.